1980
DOI: 10.1111/j.1476-5381.1980.tb07040.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF SENSORY DENERVATION ON THE RESPONSES OF THE RABBIT EYE TO PROSTAGLANDIN E1, BRADYKININ AND SUBSTANCE P

Abstract: Six to eight days after diathermic destruction of the fifth cranial nerve in the rabbit, the ocular hypertensive and miotic responses to intracameral administration of capsaicin, bradykinin, and prostaglandin E1 were greatly reduced or completely abolished. The response to substance P was not abolished. A response could still be obtained to chemical irritants 36 h after coagulation of the nerve and it is deduced that manifestation of the response is dependent upon functional sensory nerve terminals, and is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Functional studies suggest these responses are caused by nerve-released tachykinins (Butler & Hammond, 1980;Muramatsu et al, 1987), although the identity of the tachykinins released by each of the sensory nerve stimulants remains unclear. Our previous work with selective tachykinin receptor agonists (Hall et al, 1991) and antagonists (Hall et al, 1992b) indicated that activation of NK, and NK3 postjunctional receptors results in contraction in this preparation; while radioligand binding studies have demonstrated specific binding sites for substance P in iris sphincter muscle membrane preparations (Too et al, 1988;Denis et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Functional studies suggest these responses are caused by nerve-released tachykinins (Butler & Hammond, 1980;Muramatsu et al, 1987), although the identity of the tachykinins released by each of the sensory nerve stimulants remains unclear. Our previous work with selective tachykinin receptor agonists (Hall et al, 1991) and antagonists (Hall et al, 1992b) indicated that activation of NK, and NK3 postjunctional receptors results in contraction in this preparation; while radioligand binding studies have demonstrated specific binding sites for substance P in iris sphincter muscle membrane preparations (Too et al, 1988;Denis et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Bradykinin excites nociceptive sensory endings (1)(2)(3)(4)(5), producing a sensation of pain (6,7). Chemical mediators released by bradykinin from sensory endings (8)(9)(10) and from sympathetic nerve terminals (11) contribute to vasodilatation and plasma leakage at the site of inflammation. Further, as part of its inflammatory effect, bradykinin triggers the production of prostaglandin E or other arachidonic acid metabolites in some tissues, and these mediators secondarily cause a sensitization of sensory endings to bradykinin and other stimuli (12,13).…”
mentioning
confidence: 99%
“…Application of susbtance P can induce miosis and other inflammatory responses (Bill et al, 1979;Butler & Hammond, 1980;Mandahl & Bill, 1981), and it can also be released into the aqueous humor (Bill et al, 1979). Furthermore, substance P antagonists may suppress inflammation in the eye (Holmdahl et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the non-adrenergic non-cholinergic component is mediated by substance P or a similar substance (Ueda et al, 1981;Tornqvist et al, 1982;Bjorkroth, 1983;Zhang et al, 1984), and also that substance P is the neurogenic factor responsible for the miosis of the nerve-mediated response of 'Author for correspondence. the eye to irritation (Bill et al, 1979;Butler & Hammond, 1980;Soloway et al, 1981;Mandahl & Bill, 1981).…”
Section: Introductionmentioning
confidence: 99%